Reducing suicides in mental healthcare: results from a 4-year follow-up implementation study in the Netherlands (SUPRANET) - Setkowski, Kim; van Balkom, Anton J. L. M.; Hoogendoorn, Adriaan W.; Franx, Gerdien; Veerbeek, Marjolein; de Winter, Remco F. P.; Gilissen, Renske (Frontiers in Psychiatry, 2024)
In 2016, SUPRANET was launched. The SUPRANET-intervention aims at better implementing the suicide prevention guideline. An implementation study was developed to evaluate the impact of SUPRANET over time on three outcomes: suicides, registration of suicide attempts, and professionals' knowledge and adherence to the guideline. This study included 13 institutions, and used an uncontrolled longitudinal prospective design, collecting biannual data on a 2-level structure (institutional and team-level). Suicides and suicide attempts were extracted from data systems. Professionals' knowledge and adherence were measured using a self-report questionnaire. A three-step interrupted time-series analysis (ITSA) was performed for the first two outcomes. Step 1 assessed whether institutions executed the SUPRANET intervention as intended.Step 2 examined if institutions complied with the four guideline recommendations. Based on steps 1 and 2, institutions were classified as below or above average and after that, included as moderators in step 3 to examine the effect of SUPRANET over time compared to the baseline. The third outcome was analyzed with a longitudinal multilevel regression analysis, and tested for moderation.Results: After institutions were labeled based on their efforts and investments made, we found no significant difference in suicides between both groups relative to baseline. Institutions labeled as above average did register significantly more suicide attempts during the first half year of the intervention (78.8 per 100,000, p<0.001, 95%CI=(51.3 per 100,000, 106.4 per 100,000)), and as the study progressed, they continued to report a significantly greater improvement in the number of registered attempts compared to institutions assigned as below average (8.7 per 100,000 per half year, p=0.004,95%CI=(3.3 per 100,000, 14.1 per 100,000). Professionals working at institutions that invested more in the SUPRANET activities adhered significantly better to the guideline over time (b=1.39, 95%CI=(0.12,2.65),p=0.032).Institutions labeled as above average registered significantly more suicide attempts and also better adhered to the guideline compared to institutions that had performed less well. Although no convincing intervention effect on suicides was found within the study period, we do think that this network is potentially able to reduce suicides. Continuous investments and fully implementing as many guideline recommendations as possible are essential to achieve the biggest drop in suicides.